Penggunaan teknik remote sensing dalam perolehan maklumat marin - Abdullah, Adeli (1992)
Marine areas cover a large part of the earth's surface and consist of resources of economic value. Management of such vast areas required suitable marine information that can be acquired in a short duration of time. The conventional methods of obtaining marine information is by making ground measurements and sampling representative of the whole area. Such techniques are time consuming and costly and are usually limited to accessible areas. Remote sensing techniques can assits in overcoming the problems in conventional techniques. In this theses, four, studies were carried out on the use of the Landsat - 5 Thematic Mapper satellite data for deriving four types of information in marine areas. The first study involved water depth determination from satellite data based on limited depth measurements in the study area of Pulau Tioman. An algorithm was used to calculate depths which were then compared with ground check points. However, the results obtained were less satisfactory with a root-mean-square error of 4.59 metres. This accuracy is not suitable for navigation purposes. The second study was related to the determination of sea surface temperature (SST) values from satellite data over the same area. A computer program for correction of atmospheric effects and computation of SST was developed. Although ground truth values of SST were not available, the values derived from satellite data were within the range of SST values given in the "Monthly Summary of Marine Meteorological Observations" published by the Malaysian Meteorological Service. The temperatures that were derived from satellite data